PREDICTORS OF THE TIMELINESS OF CORPORATE FINANCIAL REPORTING - Sinaga, Tioma Maryanda; Syafitri, Desy Ramadhani; Gea, Wita Cristianni; Sianipar, Milka Rositi; Hou, Amin (SULTANIST: Jurnal Manajemen dan Keuangan, 2024)
Timeliness of financial reporting is an important indicator in assessing a company because it can provide accurate information for users of financial statements. This phenomenon is influenced by various internal and external factors. This study analyzes the effects of profitability, firm size, and ownership structure on financial reporting timeliness. This quantitative descriptive study was conducted on food and beverage companies listed on the Indonesia Stock Exchange (IDX) in the 2018-2021 period. Twelve companies were sampled and analyzed using multiple linear regression tests. Hypothesis testing uses the R2 (coefficient of determination) test, F test, and t test. The results show that partial profitability and ownership structure have no effect on the timeliness of financial reporting. Firm size only had a significant effect. However, profitability, firm size, and ownership structure simultaneously affected the timeliness of financial reporting (94.2%). Future studies should use other variables as predictors